The Effect of Financial Reporting Accountability on the Participation Level of UNEJ Student Support to Non-Governmental Organizations - Galang Nusantara Achmad; Zakwan Hammam; Regita Desta Sekar Sari (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to tested the effect of Financial Reporting Accountability on Unej Student Support Participation to Non-Governmental Organizations. This study uses a descriptive quantitative approach. The population in this study were active students at the University of Jember. The results showed that the value of the significance of 0.000 < 0.005, it can be concluded that the Financial Reporting Accountability variable (X) has a positive effect on the Participation Rate of UNEJ Student Support to Non-Governmental Organizations (Y). While the KD value is 0.417. From this it was found that the importance of financial reporting accountability is one of the responsibilities of non-governmental organizations information to the public, and this can also contribute to obtaining the support of public sympathizers, including students.